Association of Diet Quality with Low Muscle Mass-Function in Korean Elderly - Jung, Mikyeong (Int J Environ Res Public Health, 2019)
There is a growing body of evidence that links nutrition to muscle mass and function in the elderly, suggesting that it has an important role to play both in the prevention and management of age-related sarcopenia. Some nutrients have been studied, but less is known about the influence of overall diet quality on the loss of skeletal muscle mass and function. This study investigated the interrelationship between the recommended food score (RFS), as an indicator of overall diet quality, and muscle mass function among the Korean elderly. The sample consisted of 521 participants (263 men and 258 women), aged >65 years, who participated in the 2014–2015 National Fitness Award project. Appendicular skeletal muscle mass (ASM) was assessed by bioelectrical impedance analysis. Low muscle mass was defined as having an ASM corrected for height lower than the cutoff value established by the European Working Group on Sarcopenia in Older People. Muscle function, assessed by handgrip strength (HGS), was defined as low if it was below the 20th percentile of elderly men and women. Low muscle mass-function, defined as low muscle mass with low muscle strength (HGS), was found in 29 men (11.0%) and 22 women (8.5%). In elderly men, the low muscle mass-function group had significantly lower RFS values than the normal group after adjustments for age, body fat percentage, drinking, smoking, education, and physical activity (p = 0.019). However, there was no association between RFS and muscle mass-function in elderly women. Our findings suggest that better diet quality may be associated with higher muscle mass in elderly Korean men.